Branding the Kingdom: How Saudi Arabia Uses Global Sports to Communicate its Nation Brand - Syrén,Oscar; Cederin,Nils (2025)
Purpose: The purpose of this study is to explore how the Kingdom of Saudi Arabia communicates and presents its nation brand through global sporting events, with particular focus on LIV Golf and the Saudi Arabian Grand Prix. Research Question: How does the Kingdom of Saudi Arabia communicate its nation brand through global sporting events? Methodology: The study adopts a qualitative research design using discourse analysis. The collected empirical findings were analysed through Anholt’s (2007) Hexagon of Competitive Identity. Theoretical Framework: The theoretical framework used is Anholt’s (2007) Hexagon of Competitive Identity. Findings/Conclusion: The research question can be answered through three discursive themes – Performed Governance, Engineered Immersion and Represented Aspiration – identified across the two cases. These themes represent carefully crafted strategies through which KSA leverages global sporting events to shape a nation brand that is capable, resonant, and future-facing. The findings reveal that KSA’s branding efforts are communicated in a manner that mirrors the aspirational language of the Vision 2030 framework.
Keywords: The Kingdom of Saudi Arabia; nation brand; communication; sports